FRACTIONATION OF Cd AND Pb IN AGRICULTURAL SOIL AND THEIR DETERMINATIONS USING INDUCTIVELY COUPLED PLASMA-OPTICAL EMISSION SPECTROMETRY - Ozen, Sukran Akkus; Yaman, Mehmet (Parlar Scientific Publications (P S P), 2017)
In this study, five-step sequential extraction procedures were employed to the soils that may be polluted by anthropogenic activities, to determine five species of Cd and Pb in agricultural soils. Soil samples were collected from twelve points on an agricultural area that was located near an airport and intercity roads in Elazig-Turkey. The species including exchangeable, organically bounded, carbonate bounded, adsorbed species on Fe and Mn oxides and residual species except silicates of Cd and Pb were extracted into solution by using CaO2, Na4P2O7, Na(2)EDTA, NH2OH center dot HCl HNO3-H2O2, respectively. Mobile and total metal concentrations in soils fractions were determined by using inductively coupled plasma-optical emission spectrometry (ICP-OES). Total Cd and Pb concentrations were found in the range of 0.24-0.90 mg kg(-1) and 9.4-40.9 mg kg(-1), respectively. It was observed that total concentrations of the metals in all of the samples were lower than the permitted values. The sum of percentages of the mobile metals fractions in the first three steps was found to be lower than 50% except for Pb in one sample.
Keywords: Speciation; Toxic metals; Pollution; ICP-OES; Metal mobility